1994
DOI: 10.1128/iai.62.7.2930-2939.1994
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytokine production during the expression phase of the anticryptococcal delayed-type hypersensitivity response

Abstract: Effects of both positive and negative regulatory T cells on cellular infiltration and cytokine production during the expression phase of the anticryptococcal immune response were examined. Tamp cells, which are induced by cryptococcal antigen, significantly amplify the anticryptococcal delayed-type hypersensitivity response, whereas a cascade of T suppressor (Ts) cells inhibits the response and decreases the clearance of Cryptococcus neoformans during an infection. By using the gelatin sponge implantation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In the present study, we assessed the abilities of these two immunization protocols, which induce different cellular components, to protect mice from infection with C. neoformans. After finding that CneF-CFA immunization afforded a significant level of protection, whereas HKC immunization did not, we analyzed the ability of the HKC immunization to induce T amp cells, which are responsible for augmented IFN-␥ production (5,33). We found that HKC immunization did not induce T amp cells, suggesting that T amp cells may be important in the mechanism of clearance of C. neoformans.…”
mentioning
confidence: 97%
“…In the present study, we assessed the abilities of these two immunization protocols, which induce different cellular components, to protect mice from infection with C. neoformans. After finding that CneF-CFA immunization afforded a significant level of protection, whereas HKC immunization did not, we analyzed the ability of the HKC immunization to induce T amp cells, which are responsible for augmented IFN-␥ production (5,33). We found that HKC immunization did not induce T amp cells, suggesting that T amp cells may be important in the mechanism of clearance of C. neoformans.…”
mentioning
confidence: 97%
“…For fungal models, few data are available to implicate a particular cytokine in a specific inhibitory phenomenon. Buchanan and Murphy (7), however, reported decreased quantities of IL-2 and IFN-␥ in antigen-soaked sponges implanted in animals given cryptococcal antigen-specific suppressor-inducer (Ts1) cells, but whether the decreased production of these two cytokines resulted from the lack of stimulation of T cells involved in the normal DH response or from a more direct effect of a third factor and/or cell downregulating the production of the two cytokines is unknown. IL-5 was detected in the sponges as well, but there were no differences between those from immune and downregulated mice.…”
mentioning
confidence: 99%
“…IFN-␥ message was not upregulated during the induction phase of suppression in the MAN-specific model, i.e., Յ48 h after the injection of MAN, but it was thereafter. Finally, Buchanan and Murphy (7) reported increased production of IL-5 in suppressed mice, with decreased production of IFN-␥ and IL-2. IL-4 was unchanged.…”
Section: Discussionmentioning
confidence: 94%
“…The administration of exogenous IL-12 prevented the induction of immune suppression by UV and also prevented the activity of preformed suppressor cells (61). In one of the few fungal models in which cytokine involvement in downregulation has been studied, increased secretion of IL-5 and decreased secretion of IFN-␥ and IL-2 were detected (7).…”
mentioning
confidence: 99%